Permanent work disability due to vestibular pathology in professional drivers: a cross-sectional study (Medicina y Seguridad del Trabajo, 2022)
Introduction: vestibular disease affects occupational and personal capacities of those patients who suffers this disease.Method: observational, descriptive, analytic and transversal study. As population for study, we compare the professional drivers to the rest of professional workers. The variables used are: Autonomous community, gender, age, vestibular disease, temporal disability situation, type of contingency, contribution rates, CNAE-2009, Profession (CON-11), start of record, qualifications, expedient resolution, and the time it takes for a case resolution according to case resolution variable.Results: the total sample of study shows 597 cases, those are the cases that have been evaluated for permanent disability by vestibular disease in Spain during 2008, that eventually are qualified for permanent disability or whether not. Of the total sample of cases evaluated, 72 (12.06%) correspond to professional drivers and 525 (87.94%) to the rest of professionals. The majority gender group correlates to males, with a total of 326 cases (54.61%) with an age group superior to 55 years old (276, 46.23%). In the category of Common diseases it appears 574 cases (96.15%) and all of these, 53.94% (n=322) were initiated ex officio. Of all cases presented, 55.61% (n=270) present a resolution of not disabled and the 35.85% (n=214) with total disability. In the hypothesis testing we obtain an Odds’ ratio result of 2.42 (IC95%: 1.42-4.19) with p
Keywords: permanent disability; vestibular disease; professional driver; vertigo